A test of capillary array beam sources for very large Knudsen numbers - Steinrück, Hans-Peter; Rendulic, K.D. (Vacuum, 1986)
An experimental test of the angular distribution function of particles originating from long capillaries has been performed. Gas pressures at the tube entrance corresponding to Knudsen numbers of 10-10 were used. The results can be described very well by the elementary Clausing theory. The cosine law for gas reflection inside the tubes is fulfilled with high accuracy. No differences in the behaviour of CO, CO, N and O could be detected. The investigation is also considered to be an accurate test of the simple beam detector used in the investigation. © 1986.